Pemuridan Yang Acceptable Pada Masa Krisis Pandemic Covid-19 Di Gereja Masehi Advent Hari Ketujuh - Manuara Sinaga; Milton Thorman Pardosi; Exon Pane; Janes Sinaga (Peneliti.net, 2022)
The discipleship process which is the main mission of the church based on the Great Commission of the Lord Jesus Christ in the Gospel of Matthew 28:19-20 must always be continuous. During the Covid-19 Pandemic, the discipleship process experienced obstacles and obstacles to do, this happened due to the habit of discipleship being carried out face-to-face, while during the COVID-19 pandemic this was difficult to do. There are many things that are lost in the discipleship process during a pandemic or experiencing a slowdown due to limited interaction between communities which is often called fellowship is one of the means of church members in terms of discipleship. This situation makes all church pastors and all church members have to accept a new reality that will become a habit in worship including discipleship such as teaching the Bible. Relevant discipleship strategies must be handled with various critical ideas where young people and new converts are not only invited to study God's Word in depth, but are also invited to practice and apply the values ​​obtained in the discussion and study of the Bible in their daily lives. day. The purpose of this writing is so that every pastor can carry out in the congregation discipleship in accordance with the teachings of the Bible. This study uses a qualitative method by using a collection of bibliography of books and journals related to discipleship and service during the pandemic. Discipleship which is God's method for the plan of salvation will never fail because of these obstacles and challenges, unless God stops working in saving mankind.